The Development of English Vocabularies - Wiwiek Sundari (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2019)
Vocabularies are important parts of all languages across the globe. When vocabularies develop through human communication, the language is considered as a living language instead of a dead language. English is a living language that undergoes some developments both in grammar and vocabularies. Those developments include pronunciation, spelling, and meaning that occur in every period, that is to say, Old English, Middle English, and Modern English. In addition, English has cosmopolitan and resourcefulness characteristics. English is a cosmopolitan language since it borrows and adopts some vocabularies from other languages and resourcefulness means that English undergoes some affixation through derivation and inflection. This article discusses the metamorphoses of English vocabularies in several periods.